A study of waste water impacts of main factories on water quality of To Lich river, Ha Noi - Quy, Tran Van; Son, Tran Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 3, 2010)
Abstract. Waste water from industrial sites amounts to one third of total waste water discharged into To Lich river, and may have serious effects on the river water quality. With the total amount waste water of factories (Hanoi beer alcohol and beverage joint stock corporation (HABECO), Trang An JSC and Thuong Dinh industrial park) of 45,000 m 3 /day, these factories accounts for more than a half of total industrial waste water released into To Lich river. The analytic results of water samples taken from To Lich river show that the parameters of DO, COD, BOD 5 , TSS, NH 4 + , NO 2 - and coliform exceed  the Vietnamese Standards (QCVN 08:2008, column B 2 ). However, the concentrations of Fe and heavy metals (Zn, Cd, Cr, Cu, Mn), are lower than the Vietnamese Standards (QCVN 08:2008, column B 2 ), except the concentration of ion Pb, especially in the area from Thuong Dinh Industrial Park to the last segment of the river. The analytic results of waste water from the main factories (HABECO, Trang An JSC and Thuong Dinh industrial park, Hanoi Soap Joint Stock Company (HASO); Saovang Joint-stock Rubber Company (SRC); Tool No.1 Joint-stock Company (TJC)) show that, the parameters of TSS, BOD 5 , COD, total of nitrogen, total of phosphorus are higher than the Vietnamese standards for Industrial waste water QCVN 24:2009/BTNMT (column B). In particular, all waste water parameters of Trang An JSC are lower than the Vietnamese Standard for Industrial waste water QCVN 24:2009/BTNMT (column B), because the factory has an effective waste water treatment system. The heavy metals parameters of waste water from all factories are lower than QCVN 24:2009/BTNMT. Estimated loads of contaminants in waste water from the factories by load coefficient of IPC software show that without treatment, HABECO can release 1974 tons  of BOD, 766 tons of TSS, 8.4 tons of phosphorus and 52.5 tons of nitrogen annually; Trang An JSC can release 64.8 tons of BOD, 48.6 tons of TSS, 0.6 ton of phosphorus, 1.6 tons of nitrogen and 25 tons of oil and grease; HASO releases 30 tons of BOD, 33 tons of TSS and 5 tons of oil and grease. Thus, if the waste water is not treated, it can lead to a very seriously pollution for To Lich river.  Keywords:  To Lich river, sewage, IPC (Intergrated Pollution Control) software.